COMPULSORY LICENSING AS A TOOL FOR GLOBAL PUBLIC INTEREST: EVOLUTION, CHALLENGES, AND REFORM - Makhmudov Nizomiddin Olimjon ugli (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
This paper explores the evolving role of compulsory licensing (CL) as a critical legal and policy tool for reconciling intellectual property rights with the broader public interest in the 21st century. While the TRIPS Agreement and the Doha Declaration provide member states with considerable flexibility to issue CLs in situations of national emergency and public need, practical obstacles—including procedural complexity, vague legal definitions, and geopolitical pressures—continue to limit its application. Drawing on historical development, international legal frameworks, and recent case studies, this study examines the potential of CL not only in the context of public health, but also in addressing global challenges such as climate change, digital inequality, and food insecurity. The conclusion outlines specific legal, institutional, and policy reforms at national and international levels aimed at making CL more effective, equitable, and responsive to emerging societal needs. By reframing CL as a mechanism of innovation equity, the paper argues for a renewed commitment to cooperative global governance in the management and dissemination of patented knowledge.